Metafora dalam Poster Demonstrasi Mahasiswa Indonesia - Widyawati, Kiki (UIR PRESS, 2022)
Language has a function that is no less important, namely to convey aspirations. The aspirations of Indonesian students at the demonstration on April 11, 2022 were conveyed with hope through posters with the intention of rejecting the 3 periods, the government's performance, and cooking oil. This study aims to describe the deepest types of metaphors in the written language of the demonstration poster on April 11, 2022 conducted by Indonesian students. This study uses a qualitative approach to the method of content analysis or content analysis. The data collection technique in this study was first to find data, second to manage data, and third to present data. The data sources in this study were demonstration events and demonstration poster photos obtained by researchers from posts via Instagram and images from other internet media such as Google. The data of this research are in the form of pictures or photos of posters of demonstrations by Indonesian students on April 11, 2022. The results of the analysis show that from the thirteen poster data that the author got, there are five metaphors with abstract to concrete images, two metaphors with concrete images to abstract, two metaphors with predicative images, three metaphors with predicative images. nominative imagery, and one metaphor has a synesthesia image.